Analysis of nanoscience and nanotechnology a perspective of science, technology and society – cts (2013)
In this contribution, we discuss and analyze some aspects of nanoscience and nanotechnology, based on the approach kwon as Science, Technology and Society (STS), as well as the prospects of Philosophy of Technology. In this context, we specify the constitute the nanoscience and nanotechnology analytic research field. I is also reported its genesis and limits, emphasizing the impacts of nanotechnology in the development of the contemporary society, such as the possible benefits and problems associated to the use of nanotechnology, as well as environmental impacts, doubts and uncertainties that permeate this areas, in addition some ethical questions and public policies for the sector are analyzed.